Peran Sektor Industri Bagi Pendapatan Asli Daerah Kota Bekasi - Heri Hermawan; Fajar Ramdhani; Intan Ramdhaniatulfitri (Jurnal Riset Ilmu Ekonomi, 2022)
Economic development is characterized by the growth of the population of a country and the distribution of income. The occasional increase in national income and per capita income can be used to determine the growth rate of the economy, and it can also be used to determine the development of the level of social welfare. The acceleration of increasing economic development is often oriented towards the industrialization of economic sectors. This research seeks to explain the various contributions of the industrial sector to regional revenues. The object of research from this study is Bekasi City for the period 2007-2018. Based on the results of the study, it was explained that the Labor variable had an insignificant positive effect on Regional Original Income. Meanwhile, industrial GRDP and the number of industries have a significant positive effect on Regional Original Income in Bekasi City.